Negro poetry in Mexico. Expression of an African Presence in the Heart of Darkness - (:unkn) unknown (My University, 2019)
Just as the majority of Latin-American societies, Mexico was built from three main elements: The Native, the European, and the African. Today, however, unlike the first two which self-evidently appear whenever the Mexican world is examined, the latter seems to belong to a long-lost period that neither history nor the collective memory have kept records of. Therefore, the field of Afro Mexican Studies − which has been growing over the past few years − is revealing the legacy of the African heritage in Mexico. Conform to this design, this paper aims at exploring the issues concerning the exploitation of afronegrism in Negro poetry in Mexico
Keywords: African Research